Scheduled telephone support in internet-delivered cognitive behavioral therapy for depression: randomized controlled trials of two populations - Pihlaja, Satu; Lipsanen, Jari; Ritola, Ville; Stenberg, Jan-Henry; Joffe, Grigori (Frontiers in Psychology, 2026)
Among patients receiving internet-delivered cognitive behavioral therapy (iCBT) for depression in routine clinical practice, 101 patients were randomized to either iCBT as usual or to iCBT with add-on scheduled telephone support (STS). Depression symptoms improved in both groups. STS increased adherence, as measured by reaching mid-treatment and completing therapy. Unlike in our previously reported population at risk of dropout, STS did not enhance symptom improvement. STS significantly reduced the time in therapy compared to the at-risk population. STS enhances adherence to iCBT for depression, with an additional effect on severity only in the at-risk population.